Multiplicative Dirac System: DOI: 10.48129/kjs.13411 - Gulsen, Tuba; Yilmaz, Emrah; Goktas, Sertac (Kuwait Journal of Science, 2022)
We define a Dirac system in multiplicative calculus by some algebraic structures. Asymptotic estimates for eigenfunctions of the multiplicative Dirac system are obtained. Eventually, some fundamental properties of the multiplicative Dirac system are examined in detail.